Insomnia, Posttraumatic Stress Disorder Symptoms, and Danger: Their Impact on Victims’ Return to Court for Orders of Protection - Mazzotta, Catherine M. (Journal of interpersonal violence, 2021)
The linkages between intimate partner violence (IPV), posttraumatic stress disorder (PTSD), and insomnia have been the subject of inquiry. This study is the first to explore the associations between clinical-level insomnia, PTSD symptoms, danger, and victim socio-demographics, and whether IPV victims pursue permanent orders of protection (OPs). Data for this secondary analysis were collected through surveys, interviews, and reviews of court records on 112 women who resided in upstate New York. Women initiated actions to obtain OPs from the Domestic Violence Intensive Intervention Court (DVIIC), from 2007 to 2008. The following factors were analyzed to determine their impact on whether a woman returned to court: (a) age, (b) race, (c) employment status, (d) perceived danger, (e) PTSD symptoms, and (f) clinical-level insomnia. This study finds that the following factors significantly relate to return to court: race, clinical-level insomnia and perceived danger, clinical-level insomnia and PTSD symptoms, and severe danger level. However, in the final multivariate logistic regression, only race emerged as a predictor of whether a woman returned to court. Specifically, women of color were a third less likely to return to court than White women. These results have significant implications for future research and clinical intervention.